Modification Effect of Stone Column Dimensions and Configuration on Bearing Capacity Efficiency and Settlement in Soft Soils - Putri, Karin Dwi Jayanti; Solin, Dian Purnamawati; Farichah, Himatul (CIVED, 2023)
In airport construction, one crucial aspect to consider is the condition of the underlying soil on the runway. Following soil investigations at X project, it was determined that the soil condition is primarily characterized by soft soil layers, with Standard Penetration Test (SPT) values ranging from 4 to 10. In response to this condition, soil reinforcement was carried out using the stone column method. The objective of this study was to compare the bearing capacity and settlement of stone columns under various dimensional variations (spacing of 1.5 m, 2.0 m, 2.2 m; diameters of 0.4 m, 0.5 m, 0.6 m) and configuration patterns (square and triangular). Bearing capacity calculations were done manually, and settlement calculations were performed both manually and with the assistance program. The results were presented in tables and graphs. Using the FHWA method for bearing capacity calculations, it was found that bearing capacity increases as the diameter is increased and the spacing is reduced. Conversely, bearing capacity decreases as the diameter is reduced and the spacing is increased. The ultimate bearing capacity value for the triangular pattern installation exceeded that of the square pattern. Regarding settlement calculations after manual stone column installation, it was observed that settlement decreases as the diameter increases and the spacing between columns decreases. Settlement increases under opposite conditions. Settlement calculations using the Plaxis program focused on diameter and spacing between stone columns. During the service life, the highest settlement occurred with the triangular pattern, while the square pattern exhibited the lowest settlement.